Civil disobedience in scientific authorship: Resistance and insubordination in science. (17th August 2020) - Penders, Bart; Shaw, David M.
ABSTRACT: The distribution of credit, resources and opportunities in science is heavily skewed due to unjust practices and incentives, hardwired into science's rules, guidelines and conventions. A form of resistance widely available is to break those rules. We review instances of rule-breaking in scientific authorship to allow for a redefinition of the concept of civil disobedience in the context of academic research, as well as the conditions on which the label applies. We show that, in contrast to whistleblowing or conscientious objection, civil disobedience targets science's injustice on a more systemic level. Its further development will ease critical evaluation of deviant actions as well as helping us evaluate deviance, defiance and discontent in science beyond issues of authorship. However, empirically, civil disobedience in science engenders uncertainties and disagreements on the local status of both act and label.